Análise das provas de matemática da Olimpíada Nacional de Matemática (OLNAMAT - 2017) - Cantorín Curty, Rafael M. (2022)
The research carried out is non-experimental and descriptive level; It consisted of analyzing the results of the mathematics tests that were applied to the students of Regular Basic Education (RBE) in the "10th National Mathematical Olympiad (OLNAMAT - 2017)" conducted by students and professors of the PAS Mathematical Sciences and Information Technology of the Faculty of Education of the National University of Central Peru.  A sample of 100 mathematics tests for initial education of 04 and 05 years was taken, determining their reliability, difficulty index, discriminative power and validity coefficient. Statistical methodology was applied for quantitative data processing and some of the psychometric and edumetric statistics were calculated.  Concluding that the mathematics tests for initial education of 04 and 05 years have α = 0,623 and KR = 0,961, and α = 0,720 and KR = 0,985, respectively; that is, they are reliable for data collection; furthermore, the tests have 5 items (33%) and 7 items (47%), characterized as "difficult"; respectively, as well as 10 items (67%) with “very good discrimination”.